Exploring synergistic therapy for metabolic dysfunction-associated steatotic liver disease - Zaher, Anas; Elsaygh, Hassan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
The global epidemic of obesity has led to a surge in metabolic-associated steatotic liver disease (MASLD), which poses a significant global health burden. Current therapeutic strategies primarily focus on lifestyle modifications, weight loss interventions, and the use of pharmacological agents such as glucagon-like peptide-1 receptor agonists (GLP-1RAs). Recently, the FDA approved resmetirom, a selective thyroid hormone receptor- agonist. Both GLP-1RAs and resmetirom have individually demonstrated promising results in managing MASLD and associated metabolic disorders. However, the potential synergistic effects of combining these agents remain unexplored. This paper discusses the rationale for exploring the combination therapy of resmetirom and GLP-1RAs for managing MASLD.